Kajian Regulasi dan Proses Bisnis Penilaian Biaya PSC Cost Recovery: Studi Kasus Putusan Pajak Tahun 2020 - Aisha Salsabila; Ade Lia Septiana Putri; Alfindo Wira Yudha Pradana; Debora Nurhary Grecia Marpaung; Ilham Agista Putranto; Luthfia Almas (Jurnal Ragam Pengabdian, 2026)
This study analyzes regulatory alignment and the effectiveness of business processes in assessing cost reasonableness under the Production Sharing Contract (PSC) cost recovery scheme in Indonesia’s upstream oil and gas sector. The study is motivated by the high number of tax disputes arising from cost recovery adjustments previously approved by SKK Migas, as reflected in the 2020 Tax Court decisions. A qualitative descriptive approach is applied through regulatory analysis, case studies of Tax Court rulings, and evaluation of cost control business processes using secondary data, including statutory regulations, SKK Migas operational guidelines, and tax dispute decisions. The findings show that, at the normative level, cost recovery and oil and gas taxation regulations are aligned through the uniformity principle. However, the use of broadly defined terms in the negative list of operating costs has led to interpretative differences, moral hazards, and dual oversight between SKK Migas and the Directorate General of Taxes. These conditions contribute to increased tax disputes, legal uncertainty, and instability in state revenue.